Analisis Komparasi Daya Saing Produk Ekspor Pertanian Antar Negara Asean dalam Era Perdagangan Bebas AFTA - Prajogo Utomo Hadi; Sudi Mardianto (Jurnal Agro Ekonomi, 2004)
EnglishThe trade liberalisation under AFTA schemes commencing since 1 January 2003 would result in the more opened market in the ASEAN region and increased competition among countries in the region. The present paper aims to conduct an inter ASEAN  comparative analysis on the export growth of agricultural products as well as effect of  product composition, market distribution and competitiveness on export of agricultural products to the ASEAN region, using time-series data and Constant Market Share approach. The main findings of the analysis are as follows : (1) The Indonesia’s export growth to the ASEAN region in the 1997-1999 period was the highest one among the ASEAN countries, even higher than the world export to the same region, while in the  1999-2001 period it decreased and became slower compared than Thailand, Filipina and world; (2) Composition of the Indonesia’s export product was the best one among the ASEAN country, even though it weakened in the 1999-2001 from the previous period; (3) Market distribution of the Indonesia’s export in the 1997-1999 period was worse than Singapore’s only, but in the following period it weakened and became worse compared to Singapore and Vietnam; and (4) Competitiveness of the Indonesia’s export in the 1997-1999 period was the best one among the ASEAN countries, but weakened in the subsequent period and became worse compared to the Philippines and Thailand. It is suggested that in the future, Indonesia needs to pay more attentions on the selection of correct product composition and country destination so as to win in the increasing competition with other ASEAN countries and even non ASEAN countries.  IndonesianLiberalisasi perdagangan AFTA yang berlaku sejak 1 Januari 2003 akan menyebabkan makin terbukanya pasar di kawasan ASEAN dan makin tajamnya persaingan antar negara di kawasan ini. Tulisan ini bertujuan untuk melakukan analisis komparasi antar negara ASEAN yang menyangkut pertumbuhan ekspor produk pertanian serta efek komposisi produk, distribusi pasar dan daya saing terhadap ekspor produk pertanian ke kawasan ASEAN dengan menggunakan data sekunder deret waktu dan metode analisis Constant Market Share. Kesimpulan utama hasil analisis ini adalah sebagai berikut : (1) Pertumbuhan ekspor Indonesia ke kawasan ASEAN selama periode 1997-1999 adalah yang tertinggi di antara negara-negara ASEAN, bahkan lebih tinggi daripada pertumbuhan ekspor dunia ke kawasan yang sama, sedangkan pada periode 1999-2001 menurun dan lebih rendah dibanding Thailand, Filipina dan dunia; (2) Komposisi produk ekspor Indonesia adalah yang terbaik di antara negara-negara ASEAN, walaupun melemah pada periode 1999-2001 dibanding 1997-1999; (3) Distribusi pasar ekspor Indonesia pada periode 1997-1999 hanya kalah dari Singapura, tetapi pada periode 1999-2001 melemah dan kalah dari Singapura dan Vietnam; dan (4) Daya saing ekspor Indonesia pada periode 1997-1999 paling kuat di antara negara-negara ASEAN, tetapi pada periode 1999-2001 melemah dan kalah dari Filipina dan Thailand. Disarankan agar di masa datang, Indonesia lebih memperhatikan lagi pemilihan yang lebih tepat mengenai komposisi produk dan negara tujuan ekspornya agar dapat lebih memenangkan persaingan dengan sesama negara ASEAN lainnya dan bahkan negara-negara non ASEAN.